ANALISIS PRAKTIK PENGAJARAN MATEMATIKA DALAM PENGGUNAAN MEDIA PEMBELAJARAN DI KELAS 5 SD SWASTA BAKTI 1 - Delima Putri Nababan; Raisa Rahmadani; Fanny Alfridayanti; Elvi Mailani (Jurnal Keluarga Sehat Sejahtera, 2025)
This article is a study on how mathematics is taught in grade 5 of Elementary School (SD) with a focus on the use of learning media. The purpose of this study is to evaluate various types of media in improving students' mathematical understanding and to find problems faced by teachers in implementing them. The method used is to conduct descriptive literature research by analyzing articles related to the use of media in teaching mathematics in grade 5 of SD Swasta Bakti 1. The results of the study indicate that student interest and learning outcomes can be improved with digital, concrete, and visual media. However, obstacles remain, such as limited facilities and lack of teacher training on how to use media properly. This article suggests improving teacher skills and providing supporting tools to maximize the use of media in mathematics learning.